2023
DOI: 10.1111/ene.15704
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial carotid artery calcification morphology differs in patients with lacunar and nonlacunar acute ischemic strokes

Abstract: Intracranial carotid artery calcifications (ICACs) are a common finding on noncontrast head computed tomography (NCCT) scans, with prevalence increasing with age [1, 2]. ICACs have been associated with an increased risk of developing ischemic stroke in a prospective cohort of stroke-free patients with higher risk of stroke recurrence [3,4].Two distinct subtypes of ICAC have been recognized, involving respectively the intimal and medial layers of the arterial wall, with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…For example, another study found intracranial carotid artery calcification morphology on noncontrast computed tomography that differed in patients with lacunar and nonlacunar ischemic strokes. The association between intracranial carotid artery calcifications and lacunar stroke remains after correction for vascular risk factors [26], which was consistent with the results of this study. .…”
Section: Discussionsupporting
confidence: 92%
“…For example, another study found intracranial carotid artery calcification morphology on noncontrast computed tomography that differed in patients with lacunar and nonlacunar ischemic strokes. The association between intracranial carotid artery calcifications and lacunar stroke remains after correction for vascular risk factors [26], which was consistent with the results of this study. .…”
Section: Discussionsupporting
confidence: 92%